Mechanism of fibronectin enhancement of group B streptococcal phagocytosis by human neutrophils and culture-derived macrophages. - Hill, H R (1993)
In previous studies, we reported that fibronectin (FN) markedly enhances phagocytic uptake of antibody-coated group B streptococci (GBS) by human polymorphonuclear leukocytes. Furthermore, administration of FN along with a GBS type-specific monoclonal or polyclonal antibody to infected neonatal rats significantly enhances survival. In this study, we have examined the molecular mechanism of this enhancement through phagocyte receptors which recognize the Arg-Gly-Asp (RGD) peptide sequences contained within the FN molecule. Incubation of human polymorphonuclear leukocytes or culture-derived macrophages on coverslips coated with GRGDSP but not GRGESP markedly enhanced uptake of immunoglobulin G-coated GBS. The enhancing effect of the RGD-containing peptides was blocked by monoclonal antibodies B6H12 (directed against the integrin-associated protein) and 7G2 (directed against the beta 3-integrin receptor for RGD). These data suggest that FN enhancement of antibody-coated GBS uptake is mediated by the critical RGD sequence. Furthermore, this active peptide sequence may have an important role in immunotherapy of bacterial infections, especially in patients with decreased plasma FN concentrations.